If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 27 = 37 Reorder the terms: 27 + Y = 37 Solving 27 + Y = 37 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + Y = 37 + -27 Combine like terms: 27 + -27 = 0 0 + Y = 37 + -27 Y = 37 + -27 Combine like terms: 37 + -27 = 10 Y = 10 Simplifying Y = 10
| 1/4:x=20:400 | | 14.4y-17.998=5.6y+23.89 | | 3.25(1+3.9b)=90.7075 | | 5a-7-4a=0 | | Y+27=32 | | (4-2i)(-2-8i)= | | 6y^6(y^3-8y)+3y^9= | | -4p+4(p-8)=16-6p | | 1/3(9y-12)=8 | | -32x+46=-32x | | x-45=67 | | 3x-4+8=12 | | (4+u)(5u-1)=0 | | 4x+24=6(6x+3)+6 | | 5=6/6 | | 4n+n=-10 | | 3+m+5=14 | | x-2y+-13y=-2-6 | | -5-(-25x)+(-40x)-10=-4x-8x | | 3x+5yi=9-15i | | 4(8i)(-3+7i)= | | -12-5k=15-5k | | y=18x-9 | | x+4=1.5 | | 7/9-2/9= | | y=x^26-3x+5 | | 2n+2.62+4.6n=2.224 | | 4b+24=-2(-b-4) | | 2x-7y-t=8x | | 3(a-8)=3 | | n+2n+3n=72 | | (+24)+(-83)= |